Hubungan Lama Pemakaian Kontrasepsi Suntik Kombinasi Dengan Kadar Glukosa Darah Di Bpm “E” Kecamatan Purwosari, Pasuruan - Sri Rahayu; Siti Sundari; Erni Widiyani (SEAJOM: The Southeast Asia Journal of Midwifery, 2015)
Injectable is one of the most widely used contraceptives in Indonesia. Injectable contraceptive often causes the changes in blood glucose levels because it contains a steroid hormone with low anti-insulin. The use in the long term can even cause pancreatitis. Hormones in injectable contraceptive have opposite work against insulin. Insulin resistance causes pancreas to increasingly work harder to produce insulin. Over time the pancreas will not be able to function optimally and will have an impact on blood glucose levels. The objective of this study was to determine the relationship of the length of injectable contraceptive use to blood glucose levels among combined injectable acceptors. This study used cross sectional study design. The source of data was primary data with the respondents combined injectable acceptors in Privately Practising Midwife "E" at Purwosari Sub-district. The sampling technique was non probability sampling with a total sampling of 46 respondents who met the inclusion criteria. Data were analyzed using bivariate analysis with chi-square. In this study, 41% of women were found to have high glucose levels (>125mg/dl). A total of 53.8% of women who used combined injectable contraceptive more than two years had blood glucose levels over 125 mg / dl, but from the results of the analysis, it showed that the length of contraceptive use was not statistically significant with blood glucose levels (p value 0.095). Therefore, injectable contraceptive used in the long term must be taken into account.